The Psychological Dominance As Mediator In Relationships Between Sports Participation, And Students’ Performance - Mir Askar Khan1, Dr. Noor Muhammad, Dr. Asif Abbas Shah & Afshin Begum (Migration Letters, 2024)
This study investigates the mediating role of psychological dominance in the relationship between sports participation and students’ academic performance. The psychological dominance is about the traits such as confidence, resilience, and mental focus, is posited as a critical mechanism that translates the benefits of sports activities into enhanced academic outcomes. Using a quantitative research approach, data were collected from 344 students who actively involved in sports across educational institutions in KP, Pakistan. The results reveal that sports participation significantly fosters psychological dominance, in turn, positively impacts students’ academic performance. The mediating role of psychological dominance underlines its importance in bridging the gap between physical activity and educational success. This research contributes to growing understanding of how psychological factors amplify the benefits of sports participation on academic outcomes. The study highlights the need for integrating structured sports programs within educational curricula to develop students’ psychological strengths alongside academic skills. In this regard, the future studies should explore this relationship across diverse contexts and demographics to generalize findings further.